Aplikasi Media Tanam (Metan) untuk Pembibitan Tanaman Hortikultura di Bengkel Agribisnis - Novita, Uray Dian; Sari, Dian; Harmoko; Lubis, Ariel; Awiastian (Jurnal Pengabdian Kepada Masyarakat, 2025)
Horticultural plant nurseries at the Agribusiness workshop are one of the empowerment activities currently being developed at the Sambas State Polytechnic. The plant cultivated is cayenne pepper, which is highly volatile in price but always in demand by the community. The planting medium used to cultivate cayenne pepper has been developed over several years by the Agribusiness workshop. The growing medium used has been tested for quality and nutrient content. It is hoped that chili seedling cultivation will be able to meet the high demand for chili seedlings to be cultivated by farmers around Sambas. The initial stage of seedling cultivation involves around 5000 chili seedlings.